Penerapan Reward untuk Meningkatkan Motivasi Belajar Peserta Didik di Raudhatul Athfal Al-Khairat Kotanopan - Imelda Zulfina Lubis; Kholidah Nur; Mukhlis (PT. Willy Print Art, 2024)
This study aims to determine: Children's learning motivation before the application of rewards in RA Al-khairat Kotanopan; the application of rewards in the learning process in RA Al-khairat Kotanopan; Children's learning motivation after the application of rewards in RA Al-khairat Kotanopan. This research uses the type of Classroom Action Research (PTK). PTK is an observation of learning activities in the form of an action, which is deliberately raised and occurs in a class together. The results showed that in Cycle 1 Meeting I, the observation results showed that motivation in asking questions reached 48.38%, doing tasks 58.06%, and learning independence 58.06%. After the implementation of the reward system in the form of praise and appreciation, there was a significant increase in Cycle 1 Meeting II, where the motivation to ask questions increased to 74.19%, do tasks 58.06%, and learning independence 70.96%. Furthermore, in Cycle 2 Meeting I, motivation in asking questions reached 74.19%, doing tasks 80.64%, and learning independence 70.96%. In Cycle 2 Meeting II, the score for motivation in asking questions reached 74.19%, doing tasks 80.64%, and learning independence 70.96%. These results show that the application of rewards is effective in increasing student learning motivation.